Analisis Portofolio Optimal Menggunakan Model Markowitz Pada Saham Jakarta Islamic Index Periode 2019-2024 - Silviani, Dewi; Puspitasari, Endah Yuni; Irawan, Irawan (Jurnal Akuntansi & Keuangan Unja, 2025)
This study aims to determine the optimal portfolio formation using the Markowitz model on Jakarta Islamic Index (JII) stocks for the2019-2024 period. The population in this study is all 30 Jakarta Islamic Index stocks for the 2019- 2024 period, while the sample is 12 stocks. Data analysis was conducted using the Markowitz model which begins by collecting monthly closing stock prices, calculating realized returns, expected returns, risks, covariances, and correlations until an optimal portfolio is obtained. This testresulted in four stocks that became the optimal portfolio with maximum profits, namely ICBP, ADRO, ANTM, and EXCL with anexpected return of 1.08% and a risk of 6.26%. On the other hand, the minimum risk consists of ICBP, INDF, INCO, EXCL, UNTR, and ADRO with an expected return of 0.44% and a risk of 4.37%. These results confirm that the application of the Markowitz model can help investors in determining the optimal stock combination according to risk preferences.